The Influence Of Leadership Style, Work Discipline And Work Ethic On Employee Performance At The Secretariat Of The Regional House Of Representatives Of North Sumatra Province - Lubis, Mega Agnesi; Anwar, Yohny; Alfahmi, Muhammad (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to analyze the influence of leadership style, work discipline and work ethic on employee performance in the Secretariat of the Regional House of Representatives of North Sumatra Province. The research method used in this study is using a quantitative model. The population in this study is all employees as many as 323 people at the Secretariat of the Regional People's Representative Council of North Sumatra Province. The sampling technique uses probability sampling draw.The number of samples in this study was 76 respondents. The data sources used in this study are primary and secondary. The technical data analysis in this study was carried out using Multiple Linear Regression using the SPSS Application. The results of data analysis show that leadership style has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance and work ethic has a positive and significant effect on employee performance.